Case studies in heritable vascular disease: Proceedings of the UTHealth Houston Multidisciplinary Aortic Conference - Milan Jaiswal, BA; Lucas Ribe, MD; Rana O. Afifi, MD; Yuki Ikeno, MD; Alana C. Cecchi, MS; Bihong Zhao, MD, PhD; Akiko Tanaka, MD, PhD; Gustavo S. Oderich, MD; L. Maximilian Buja, MD; Dianna M. Milewicz, MD, PhD; Siddharth K. Prakash, MD, PhD; Anthony L. Estrera, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Heritable thoracic aortic disease is caused by dominantly inherited mutations in more than a dozen genes, including TGFB2 mutations that cause Loeys-Dietz syndrome. McGovern Medical School at UTHealth Houston convenes a regular conference that includes cardiothoracic and vascular surgeons, cardiologists, geneticists, radiologists, and pathologists to formulate multidisciplinary approaches for the management of complex heritable thoracic aortic disease cases. In this report, we highlight the unique management of individuals with distinct presentations of Loeys-Dietz syndrome owing to TGFB2 mutations.